Dampak Permasalahan Pinjaman Online Dan Perlindungan Hukum Bagi Konsumen Dalam Perjanjian Pinjaman - Nulqorim, Karim; Ansari, Teuku Syahrul (Peneliti.net, 2024)
They provide a solution without considering the potential future consequences. Consumers of online lending services often face difficulties that have a significant influence on them. One such issue is the discomfort, feelings of blackmail, dread, and intimidation experienced throughout the process of collecting payments. In addition to breaking the law, this online lender's actions violate human rights, as stated in Article 29 Paragraph (1) and Article 30 of Law No. 39 of 1999 concerning Human Rights. With the passage of laws like Law 8 of 1999, Financial Services Authority Regulation Number 77/POJK.01/2016, and Law Number 19 of 2016, customers and service users of online loans are hoping for some sort of official protection. This one is on a lower level. So, the author hopes for betterment and enlightenment in the realm of government.